2003
DOI: 10.1002/jmri.10262
|View full text |Cite
|
Sign up to set email alerts
|

Normal human left and right ventricular dimensions for MRI as assessed by turbo gradient echo and steady‐state free precession imaging sequences

Abstract: Purpose:To establish normal ranges of left ventricular (LV) and right ventricular (RV) dimensions as determined by the current pulse sequences in cardiac magnetic resonance imaging (MRI). Materials and Methods:Sixty normal subjects (30 male and 30 female; age range, 20 -65) were examined; both turbo gradient echo (TGE) and steady-state free precession (SSFP) pulse sequences were used to obtain contiguous short-axis cine data sets from the ventricular apex to the base of the heart. The LV and RV volumes and LV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
495
13
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 665 publications
(572 citation statements)
references
References 23 publications
52
495
13
5
Order By: Relevance
“…The greatest differences were noted for female volunteers, where the mean EDV and LVM parameters were 12 ml and 11 g lower, respectively, at 3.0T when compared to the previous pooled 1.5T data reported by Kawel‐Boehm et al11 If the individual articles that contribute to this published range are scrutinized more closely, the best agreement to our 3.0T mean EDV (120 ml) is found in the work by Maciera et al,3 who obtained a mean EDV of 126 ml for their cohort of female volunteers in the 50–59 years age decade at 1.5T. Similarly, the closest agreement to our mean LVM (87 g) is reported in the work by Alfakih et al,1 who obtained a mean LVM of 88.1 g for their cohort of female volunteers in the 40–65 years age range at 1.5T. In other words, although some discrepancy exists between the pooled 1.5T data, there are individual contributions that agree quite closely with our findings at 3.0T.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The greatest differences were noted for female volunteers, where the mean EDV and LVM parameters were 12 ml and 11 g lower, respectively, at 3.0T when compared to the previous pooled 1.5T data reported by Kawel‐Boehm et al11 If the individual articles that contribute to this published range are scrutinized more closely, the best agreement to our 3.0T mean EDV (120 ml) is found in the work by Maciera et al,3 who obtained a mean EDV of 126 ml for their cohort of female volunteers in the 50–59 years age decade at 1.5T. Similarly, the closest agreement to our mean LVM (87 g) is reported in the work by Alfakih et al,1 who obtained a mean LVM of 88.1 g for their cohort of female volunteers in the 40–65 years age range at 1.5T. In other words, although some discrepancy exists between the pooled 1.5T data, there are individual contributions that agree quite closely with our findings at 3.0T.…”
Section: Discussionsupporting
confidence: 86%
“…These patterns of change over time are most similar to those reported by Hudsmith et al2 at 1.5T, where they compared cohorts of volunteers in groups with age stratification <35 years and >35 years. Similar patterns of change over time are also presented by Alfakih et al1 and Macieira et al3 at 1.5T.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have reported different values for the upper limit of normal LV mass 13, 28, 29. To address these differences, CMR data on LV mass and concentricity were obtained from 44 healthy subjects (22 men and 22 women).…”
Section: Methodsmentioning
confidence: 99%
“…The interventricular septum was included in the left ventricular mass. In the basal slices, the following criteria for inclusion in the ventricular volume were used: 1) when the cavity was only partially surrounded by ventricular myocardium in end-systole or end-diastole, only the part up to the junction with atrial tissue was included in the ventricular volume (6); 2) when the pulmonary or aortic valve was visible in the basal slice, contours were drawn up to the junction with the semilunar valves (6,13). In the apical area, major trabeculations and the moderator band were included in the left or right ventricular mass (13).…”
Section: Cmr Analysismentioning
confidence: 99%
“…Compared to the previously used spoiled gradient-echo sequences, SSFP provides better bloodmyocardial contrast, higher image quality, and faster acquisition times (4). Better blood-myocardial contrast in SSFP imaging results in statistically significantly higher end-diastolic volumes (EDV) and end-systolic volumes (ESV), lower mass, and lower ejection fraction (EF) (5,6). Therefore, SSFP-derived data cannot be compared to data obtained with spoiled gradient echo sequences.…”
mentioning
confidence: 99%